Study of influence of boron and rare-earth metals on impact elasticity - N. V. Nevar; Ju. N. Fasevich (Литьë и металлургия)
In the offered work there are presented the investigations of impact elasticity of experimental samples of cast material, which may be used for production of articles, working in conditions of abrasive and hydroabrasive damage conjugated with impingement attacks. There is studied fractures pattern of cast samples with different boron content, and also additives of rare-earth metals. There are determined the types of the modifying agents, most efficiently affecting on such feature as resistance to brittle failure of the developed alloys.